2018
DOI: 10.1080/03019233.2018.1510874
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of fluid flows in square billet moulds, using a new nozzle orientation in the presence of an in-mould rotary electromagnetic stirrer

Abstract: An electromagnetic field simulation along with a fluid flow analysis model were developed, to study the effect of the submerged entry nozzle's (SEN) angle of rotation, together with a rotational electromagnetic field, on the turbulent liquid steel flow within a curved, square mould of a billet continuous caster. The Realisable-k-ɛ turbulence model and the volume of fluid multiphase model were implemented, so as to simulate the effect of turbulent fluid flow on the shape of the top liquid steel meniscus. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…[4,5] The flow of steel in the mould can be improved or aggravated by adjusting nozzle characteristics such as the number of ports, port angles, and immersion depth of the submerged entry nozzle (SEN). [6,7] The functions of the SEN include preventing liquid steel from spattering and improving the billet temperature and flow-field distribution. [8,9] Zhang et al [10] studied the effect of SEN-type on flow, heat transfer, and solidification in the mould and found that the shell thickness of the straight SEN was the thickest in the mould zone but became thinner beyond 0.9 m from the meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The flow of steel in the mould can be improved or aggravated by adjusting nozzle characteristics such as the number of ports, port angles, and immersion depth of the submerged entry nozzle (SEN). [6,7] The functions of the SEN include preventing liquid steel from spattering and improving the billet temperature and flow-field distribution. [8,9] Zhang et al [10] studied the effect of SEN-type on flow, heat transfer, and solidification in the mould and found that the shell thickness of the straight SEN was the thickest in the mould zone but became thinner beyond 0.9 m from the meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–6 ] However, with the development of large‐section equipment and technology in recent years, high attention has been paid to how to use the kinetic energy of the molten steel in the submerged entry nozzle (SEN) under mass conservation to regulate the macroscopic transport behavior in the mold. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, with the development of largesection equipment and technology in recent years, high attention has been paid to how to use the kinetic energy of the molten steel in the submerged entry nozzle (SEN) under mass conservation to regulate the macroscopic transport behavior in the mold. [7][8][9] Earlier, Yokoya et al [10,11] tried to add a swirling blade on the upper part of the conventional straight through nozzle to disperse the kinetic energy of the molten steel from vertical downward to surrounding, and then form a horizontal swirling flow to achieve the purpose of superheating dissipation. Based on the idea, Sun et al [12,13] proposed a quad-furcated swirling flow nozzle (SFN) to make the molten steel flow out of the side hole that can swirl to wash the initial solidified shell, and the feasibility of improving the internal quality of strand by SFN through the establishment of a 3D numerical model including flow, heat transfer, solidification, and solute transport and the industrial production was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…As the section of the round bloom increases, the solidification rate decreases significantly, and the flow field distribution in the mold is different from that in the small cross section. Reasonable control of molten steel flow in round bloom mold can effectively reduce both internal and surface defects [ 1 , 2 ]. The main measures to improve the mold flow are changing the nozzle structure and applying mold electromagnetic stirring (M-EMS).…”
Section: Introductionmentioning
confidence: 99%